Saatnya UMKM Naik Kelas: Sosialisasi Pemanfaatan Digital Marketing untuk Masyarakat Desa - Khairurrizqo, Khairurrizqo (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Empowering Micro, Small, and Medium Enterprises (UMKM) is a key pillar in local economic development, particularly in rural areas. This community service program aims to enhance digital marketing skills among UMKM entrepreneurs in Desa Ledug, Kecamatan Kembaran, Kabupaten Banyumas. Through training sessions and mentoring, participants are taught various digital marketing techniques that can help them expand their market reach and increase product sales. The methodology used is a combination of educational sessions, hands-on practice, and continuous mentoring. The expected outcome of this program is to encourage local economic development by empowering UMKM through the effective use of digital technology.